Enhancing Digital Learning Outcomes: The Combined Impact of Competence and Psychological Traits - Elma Nurjannah; Riana T Mangesa; M. Miftach Fakhri; Muhammad Fajar B; Sanatang Sanatang; Fitria Arifiyanti (Online Learning In Educational Research (OLER), 2025)
The rapid shift towards digitalization, accelerated by the COVID-19 pandemic, requires a reassessment of problem-solving strategies in the education system. This study aims to investigate the interactions between Digital Competencies, Psychological Traits, Digital Readiness, and Awareness, and their combined influence on Learning Outcomes. The study utilized a quantitative, cross-sectional design, focusing on university students engaged in digital learning environments in higher education. Data were collected from 467 students through a validated online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that Digital Competence and Psychological Traits significantly and positively influence Learning Outcomes, both directly and indirectly through the mediating role of Digital Readiness and Awareness. The findings emphasize the need for a holistic approach in education, which integrates technical skills and psychological readiness to enhance academic success in an increasingly digital learning environment. This study also highlights the need for further research with a longitudinal design to explore the long-term effects of digital competency and awareness interventions. Recommendations for future research include examining additional factors such as social support and technology access to further strengthen digital readiness and learning outcomes